(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
Both a good classroom setting and fostering autonomy in our learners are contents of the curriculum in the Infant Education stage. Interiorizing logical-mathematical aspects is a key factor to get to know the environment around daily situations and us. Mathematical thinking comes from everyday situations students are exposed. Therefore, it is important to achieve the understanding of these scientific concepts using tools like mechanisms of double entry tables and their implementation in the classroom. The classroom setting in learning corners inside the classroom provides students with the possibility of choosing where they want to work. This technique enables individual and group analysis on a weekly basis. This assessment will take place both individually and in groups. The register will be done using double-entry tables displayed in the assembly area. This way, thinking schemes are promoted helping learners to solve problems and develop deductive thinking, within and outside the school environment.